Effectivity of different concentartions of soil Inoculant (rhizobium japonicum) on the germination and growth of soybeans (Glycine max). - Morante, James Paul (Iloilo City UPHSI, 2001)
Soybeans (Glycine Max) has ever since been a good source of protein. Due to growing demands, yield increase had been a must for farmers. Thus, the utilization of all knows methods to increase yield had been a great concern. This paved the way for the use of soil inoculant which is the main concern of the study. Soil inoculant used was Rhizobium japonicum and applied to soybeans at different concentrations based on a standard ratio released by the Department of Agriculture. The study had 4 treatments - treatment 1: nitrogen only which served as positive control, treatment 2: without nitrogen which served as negative control, treatment 3: 100% of the standard ratio R. japonicum and treatment 4: 200% of the standard ratio of R. japonicum. After planting, watering was done everyday and germination was recorded every 2 days for a duration of 10 days. Treatment 3 which was applied with 100% of standard ratio of soil inoculant had the highest germination rate. Harvesting of soybeans was done when the pods turned brown. Based on the wet and dry weights, treatment 2 which was applied with phosphorus only showed the highest yield. The least yield was obtained from Treatment 1 which was applied with the right nitrogen and phosphorus requirement. However, no significant difference was noted among the means of the treatments after using one-way analysis of variance (ANOVA) at a = 0.05. This means that the means of the results in germination rate and yield based on both dry and wet weights did not vary significantly.
Research II : Research Manuscripts
Keywords: Soybeans